2004
DOI: 10.1097/00004872-200410000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and target organ damage in untreated essential hypertensives

Abstract: These results from a representative sample of untreated middle-aged hypertensives show that: (i) the metabolic syndrome is highly prevalent in this setting and (ii) despite similar ambulatory blood pressure values, patients with metabolic syndrome have a more pronounced cardiac and extracardiac involvement than those without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
128
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 40 publications
27
128
3
4
Order By: Relevance
“…This observation is in agreement with previous studies in hypertensive and in normotensive subjects with signs of insulin resistance. [20][21][22] The present study also showed that of the five components of the MS body size and BP were particularly associated with LVM but also blood glucose was independently related to cardiac dimensions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This observation is in agreement with previous studies in hypertensive and in normotensive subjects with signs of insulin resistance. [20][21][22] The present study also showed that of the five components of the MS body size and BP were particularly associated with LVM but also blood glucose was independently related to cardiac dimensions.…”
Section: Discussionsupporting
confidence: 74%
“…The observation of an early dysfunction of the diastolic ventricular filling is, however, one of the first findings of such abnormality in subjects with MS observed in a population sample, confirming data detected in the American Indian population. 24 In patients from the Hypertension Outpatient Clinic, the corresponding data are, however, conflicting since differences in diastolic function between subjects with and without MS were present in a study 25 and absent in another, 22 possibly because differences were obscured by the equally elevated BP values in both groups. Regarding the possible phenomenon of the pseudo-normalization of the E/A ratio, which occurs in subjects with particularly deteriorated diastolic function, it does not appear to influence the results of the present study since it should have played against our observation of a reduced E/A.…”
Section: H Ig H B Lo O D P R E S S U R E H Ig H F a S T In G B G L O mentioning
confidence: 99%
“…12,23,24 In hypertensive patients without manifest vascular disease, the metabolic syndrome has been shown to be associated with increased intima-media thickness and left ventricular hypertrophy as well as with increased incidence of cardiovascular events. [25][26][27][28][29] It is not yet known whether the metabolic syndrome still is a predictor of new cardiovascular events in hypertensive patients with already clinically manifest cardiovascular disease. If the risk for future cardiovascular events in patients with hypertension and the metabolic syndrome is higher compared to those without the metabolic syndrome, these patients may benefit from more aggressive treatment of blood pressure and other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that subjects with the metabolic syndrome often present with increased LV mass (and LV hypertrophy) [10,11] The Framingham Heart Study evaluated LV mass using echocardiography and observed that increased LV mass is an independent predictor of clinical events such as heart failure, ischemia, ventricular arrhythmia, and sudden cardiac death [12]. Accordingly, reduction of LV mass is important for improvement of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that patients with the metabolic syndrome often present with increased left ventricular (LV) mass (and LV hypertrophy) [10,11]. The Framingham Heart Study evaluated LV mass using echocardiography in relation to long-term clinical outcome, and observed that an increase in LV mass is an independent predictor of clinical events, including death, attributable to cardiovascular disease [12].…”
Section: Introductionmentioning
confidence: 99%